Réponses

2012-10-30T18:19:38+01:00

(2x+3)²-(x+1)²=(2x+3-x-1)(2x+3+x+1)=(x+2)(3x+4)

 

16(x-1)²-(2x-5)²=(4(x-1))²-(2x-5)²=(4x-4-2x+5)(4x-4+2x-5)=(2x+1)(6x-9)=3(2x+1)(2x-3)

 

(4x+3)²-2(4x+3)(x+2)=(4x+3)(4x+3-2(x+2))=(4x+3)(4x+3-2x-4)=(4x+3)(2x-1)

 

49-(x+2)²=7²-(x+2)²=(7-x-2)(7+x+2)=(5-x)(x+9)

 

x²-25+2(x-5)(x+3)=(x²-5²)+2(x-5)(x+3)=(x-5)(x+5)+2(x-5)(x+3)=(x-5)(x+5+2(x+3))

=(x-5)(x+5+2x+6)=(x-5)(3x+11)

2012-10-30T18:27:54+01:00

(2x+3)²-(x+1)²= (4x²+9+12x)-(x²+1+2x)=4x²+9+12x-x²-1-2x=3x²+8+10x

 

16(x-1)²-(2x-5)²=16(x²+1+2x)-(4x²+25-20x)=...

 

(4x+3)²-2(4x+3)(x+2)=

 

49-(x+2)²=7²-(x+2)²=

 

x²-25+2(x-5)(x+3)=